WEBSITE FOR ONLINE OR BLENDED TEACHING OF GENETICS FOR THE DEVELOPMENT OF KNOWLEDGE AND SKILLS IN BIOLOGY STUDENTS - Torres, Claudia Marissa Calderon (PUPIL: International Journal of Teaching, Education and Learning, 2024)
Genetics is the science that studies the transmission and variation of the hereditary information of organisms stored in DNA. Currently, Genetics encompasses a strategic set of knowledge and skills that biology professionals must have, in such a way that those who do not have this knowledge, techniques and even theories, run the risk of not entering a job position. Objective. This work presents a web page developed to facilitate the learning of Genetics knowledge. This project brings together participants who have carried out scientific and professional work, have taught genetics courses and know the problems of teaching and learning genetics. Results. The developed website (www.genetica.abaco2.org) incorporates: 1) Educational texts for the development of knowledge, skills and competencies on specific topics; 2) Multiple choice questionnaires for self-assessment; 3) Hardy-Weinberg simulator; and 4) Evaluation of the understanding of educational texts through the application of quick questionnaires. The texts are focused on undergraduate students of careers in the biological-medical area. The effect on learning of the contents of the website with the topic of genetic recombination was evaluated by comparing the learning in two groups of students: group A (133 students) with prior reading of the educational text and group B (119 students) without reading of the educational text. Through statistical analysis with the Z test it was found that group A had higher percentage (75.6% vs. 55.8%; P<0.01) of correct answers when answering a test of 10 questions. Conclusions: The designed website is a resource that teachers and students can benefit from by facilitating the teaching-learning process of Genetics.